RANCANG BANGUN MOBILE ROBOT METAL SWEEPER - Hafizh, Muhammad Taufiqul; Rasmana, Susijanto Tri; Pamungkas, Johan (Journal of Control and Network Systems (JCONES), 2016)
In the military field, the country's defense system has developed a robot in the field of high-tech military and intelligence and accuracy are high enough in order to help maintain a more optimal state. For example Battalion Cavalry fighting vehicles were used to attack and destroy enemy bases and bomb disposal robots designed to assure the safety of bomb disposal officers. Mobile robots are used to detect metal objects in the arena.                    In this study, for setting the path on the mobile robot so that the mobile robot can walk with a straight writer using fuzzy Sugeno, because it is a flexible method in terms of a parameter can change under certain conditions and adapting to the changes that are influenced by the environment.                    Results from this study, the percentage of the sweeping success of the arena by 70%, for the success of detecting metal objects with metal objects the size of 2cm x 10 cm by 80%, as well as to the success of detecting metal objects with metal objects the size of 2cm x 20cm by 100%. Key words: Mobile Robot, Fuzzy, Metal Sweeper.In the military field, the country's defense system has developed a robot in the field of high-tech military and intelligence and accuracy are high enough in order to help maintain a more optimal state. For example Battalion Cavalry fighting vehicles were used to attack and destroy enemy bases and bomb disposal robots designed to assure the safety of bomb disposal officers. Mobile robots are used to detect metal objects in the arena. In this study, for setting the path on the mobile robot so that the mobile robot can walk with a straight writer using fuzzy Sugeno, because it is a flexible method in terms of a parameter can change under certain conditions and adapting to the changes that are influenced by the environment. Results from this study, the percentage of the sweeping success of the arena by 70%, for the success of detecting metal objects with metal objects the size of 2cm x 10 cm by 80%, as well as to the success of detecting metal objects with metal objects the size of 2cm x 20cm by 100%. Key words: Mobile Robot, Fuzzy, Metal Sweeper.